1978
DOI: 10.1002/1097-4679(197804)34:2<393::aid-jclp2270340228>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The separation of organics from depressives with ability-and personality-based tests

Abstract: Previous research has indicated that ability-oriented organicity tests are of limited value in the separation of brain-damaged from schizophrenic patients in psychiatric hospitals. In the present study the capabilities of nine ability test measures and the MMPI Depression scale to differentiate organics from depressives were evaluated. Only six of the nine ts used to evaluate the differences between the two groups were significant at the 0.5 level and, after the samples were levelled for age, education and IQ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Compared to the relatively robust research supporting cognitive deficits in healthy depressed persons (Breslow, Kocsis, & Belkin, 1980;Deptula & Yozawitz, 1984;Fischer, Sweet, & Pfaelzer-Smith, 1986;Savard, Rey, & Post, 1980;Shipley et al, 1981;Sternberg & Jarvik, 1976;Watson, Davis, & Gassen, 1978), researchers have only recently begun to support a significant relationship between depression symptomatology and cognitive functioning within the multiple sclerosis (MS) population. Several studies have failed to find a significant relationship between cognitive impairment and depression in persons with MS (DeLuca, Barbieri, & Johnson, 1994;Grafman et al, 1991;Minden et al, 1990;Rao, Leo, & St. Aubin-Faubert, 1989).…”
mentioning
confidence: 99%
“…Compared to the relatively robust research supporting cognitive deficits in healthy depressed persons (Breslow, Kocsis, & Belkin, 1980;Deptula & Yozawitz, 1984;Fischer, Sweet, & Pfaelzer-Smith, 1986;Savard, Rey, & Post, 1980;Shipley et al, 1981;Sternberg & Jarvik, 1976;Watson, Davis, & Gassen, 1978), researchers have only recently begun to support a significant relationship between depression symptomatology and cognitive functioning within the multiple sclerosis (MS) population. Several studies have failed to find a significant relationship between cognitive impairment and depression in persons with MS (DeLuca, Barbieri, & Johnson, 1994;Grafman et al, 1991;Minden et al, 1990;Rao, Leo, & St. Aubin-Faubert, 1989).…”
mentioning
confidence: 99%
“…Among the tests that have failed to discriminate organic from psychiatric groups (and, particularly, from schizophrenics) satisfactorily in various studies are the Bender-Gestalt (Watson, 1968), the Halstead tests (Lacks, Colbert, Harrow, & Levine, 1970;Watson, Thomas, Felling, & Andersen, 1968), the Trail-Making Test (Orgel & McDonald, 1967;Smith & Boyce, 1962;Watson, Thomas, Felling, & Andersen, 1969), the Memory-For-Designs (Watson, 1968), the Draw-A-Person (Watson, 1967), and the Minnesota Percepto-Diagnostic Test (Watson & Uecker, 1966 Davis & Gasser, 1978), the Background Interference Procedure variation of the Minnesota Percepto-Diagnostic Test (BIP-MPD; cf. Several investigators have reported themselves unable to differentiate the two with various ability measures.…”
mentioning
confidence: 99%
“…These measures include the Psychiatric-Organic (P-0) scale of the Minnesota Multiphasic Personality Inventory (MMPI), an empirically constructed 56-item measure designed to separate organics from a wide spectrum of functional psychiatric groups (Watson & Plemel, 1978). Additionally, three studies (Watson, 1973;Watson, Davis & Gasser, 1978;Watson & Plemel, 1978) have suggested that combinations of ability and personality tests are more useful in the separation of organics from functional patients than either type of measure used alone. Therefore, the capability of the strongest of our three ability tests to separate organic from functional groups in combination with the P-0 scale also was evaluated.…”
mentioning
confidence: 99%
“…Recently, though, a successful new approach that uses an ability-based test and a personality test in combination has proven to be more efficient than either of the two approaches described above in the task of separating brain-damaged from psychiatric patients (Watson, 1973;Watson, Davis, & Gasser, 1978;. In a pioneer study, Watson et al (1981) proved not only that the combined use of an abilitybased and personality test resulted in greater mean hit rates, but also that the specific combined use of the SDMT and the MMPI (P-0), among other combinations of tests, produced the most encouraging results by correctly identifying 90% of the organic sample and 79% of the functional/psychiatric sample, an overall mean hit rate of 84.5%.…”
mentioning
confidence: 99%